Pressure Dependence on the Thermal Conductivity of H‐ and J‐type Nanocomposites (Adv. Mater. Interfaces 21/2022). Issue 21 (22nd July 2022) - Hong, Younggi; Goh, Munju
Abstract : Pressure Dependence on Thermal Conductivity of H‐ and J‐Type Composites The H‐ and J‐type composites show a different pressure dependence of the thermal conductivity as reported in article number 2200027 by Younggi Hong and Munju Goh. As the pressure increases, the H‐ and J‐type aggregation composite demonstrates a different thermal conductivity pathway in the other direction and other conductive fillers are guided by H‐ and J‐ type aggregation. It is expected to be advantageous for heat dissipation applications to electric devices.